The Effect of Rebozo Technique on the Length of Time for Active Phase I Labor in the Noemuti Health Center Area in 2023 - Fitriyaningsih Fitriyaningsih; Samfriati Sinurat; Ramatian Simanihuruk (Jurnal EduHealth, 2023)
There are still numerous problems in Indonesia, including prolonged labor that can murder mothers and infants. The rebozo technique is a physiological endeavor to prevent prolonged labor that can accelerate or shorten the active phase of labor. In 2023, the objective is to ascertain the impact of the rebozo technique on the duration of active phase I labor in the Noemuti Health Center Region.Research technique The research design is a Quasi-Experiment employing a One-Group Pretest-Posttest Design with a control. 30 respondents in the population, 15 in the experimental group and 15 in the control group as the cohort. The investigation lasted one month, from April 2022 to May 2023. The rebozo technique intervention group had a rank value of 3.8 and a standard deviation of 2.0, and the p value was greater than 0.005, so it can be concluded that there was a significant difference between the intervention group and the control group. With a p value of 0.003 0.005, mothers who were intervened by the rebozo technique were able to reduce labor time to 6 hours and reduce pain. The conclusion The rebozo technique should be communicated to mothers and families at term gestation regarding the intervention of the rebozo technique if done regularly, it is hoped that when the mother enters the inpartu period, it can accelerate the opening of the cervix and the decrease in the fetal head in laboring mothers during the active phase I, thereby shortening the duration of labor.